Intervening Alokasi Belanja Pada Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Ekonomi Pemerintah Daerah Jawa Tengah - syafnita (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This study aims to examine and analyze the effec to flocal government financial performance as measured by the independen ceratio, dependency ratio, degree of decentralization, PAD effectiveness ratio, degree of BUMD contribution and debt to income ratio on capital expenditure allocation and economic growth. As well as to examine and analyze the effect of local government financial performance as measured by the independence ratio,dependency ratio, degree of decentralization, PAD effectiveness ratio,degree of BUMD contribution and debt to incomeratio on economic growth to mediated capital expenditure allocation. This research is a correlational study with acausal relationship, namely to examine the effect of regional financial performance on economic growth through the allocation of capital expenditures as an intervening variable. The sample in this study was 35 Regency/City Governments in Central Java. The data analysis technique used path analysis with SEM (Structural Equation Modeling). Theresults showed (1)Financial independence, financial dependence and The degree of BUMD's contribution did not havea direct effect on the allocation of capital expenditures. The degree of decentralization, the effectiveness of PAD and the debt to income ratio have a direct and significant effect on the allocation of capital expenditures. (2) Financial independence, degree of decentralization and effectiveness of PAD have a direct effect on economic growth. Financial dependence, degree of BUMD’s contribution, debt to income ratio and capital expenditure allocation do not have a directand significant effect on economic growth. (3) Capital expenditur eallocation mediates the effect of the degree of decentralization, the effectiveness of PAD and the degree of BUMD's contribution on economic growth. However, the capital expenditure allocation does not mediate the effect of financial independence, financial dependence and the debt to income ratio to economic growth